Bioactive cationic peptides as potential agents for breast cancer treatment (2021)
ABSTRACT: Breast cancer continues to affect millions of women worldwide, and the number of new cases dramatically increases every year. The physiological causes behind the disease are still not fully understood. One in every 100 cases can occur in men, and although the frequency is lower than among women, men tend to have a worse prognosis of the disease. Various therapeutic alternatives to combat the disease are available. These depend on the type and progress of the disease, and include chemotherapy, radiotherapy, surgery, and cancer immunotherapy. However, there are several well-reported side effects of these treatments that have a significant impact on life quality, and patients either relapse or are refractory to treatment. This makes it necessary to develop new therapeutic strategies. One promising initiative are bioactive peptides, which have emerged in recent years as a family of compounds with an enormous number of clinical applications due to their broad spectrum of activity. They are widely distributed in several organisms as part of their immune system. The antitumoral activity of these peptides lies in a nonspecific mechanism of action associated with their interaction with cancer cell membranes, inducing, through several routes, bilayer destabilization and cell death. This review provides an overview of the literature on the evaluation of cationic peptides as potential agents against breast cancer under different study phases. First, physicochemical characteristics such as the primary structure and charge are presented. Secondly, information about dosage, the experimental model used, and the mechanism of action proposed for the peptides are discussed.